Mendidik Anak di Era Digital: Peran Konten @claycliffhartono untuk Kesadaran Parenting - Kamilah, Salwa Ridha; Achmad, Zainal Abidin (Jurnal Nomosleca, 2024)
The study aims to describe the content of TikTok The Hartono's Family @claycliffhartono as a parenting education media. The research findings show that this account has succeeded in getting significant interactions in the form of likes, comments, and viewers. This study uses a qualitative narrative ethnography method by interviewing 8 informants who are regular audiences of the account. The stages of data analysis include data reduction, data display, and conclusions. This is made possible by the various features provided by TikTok for its users. In addition, the audience generally prefers content related to emotional management. In fact, it has succeeded in implementing a similar parenting pattern. The parenting models that the audience wants to apply are authoritative parenting, attachment parenting, and free-range parenting.